2018
DOI: 10.1016/j.nmd.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel MYH7 founder mutation causing Laing distal myopathy in Southern Spain

Abstract: MYH7 gene mutations are associated with wide clinical and genetic heterogeneity. We report a novel founder mutation in MYH7 in Southern Spain (Andalucía). We studied two index patients and 24 family members from two apparently independent families by physical examination, serum creatine-kinase, muscle MRI, sequencing studies and genetic linkage analysis. Sixteen individuals were heterozygous for a (p.R1560P) variant in the MYH7 gene. Haplotype was consistent with a common ancestor for the two families. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Because the human mutation has an autosomal dominant inheritance pattern, we generated transgenic animals expressing UNC-54(mut)::GFP in a wild-type genetic background; worms expressing GFP alone and UNC-54(wt)::GFP fusion protein in the same wild-type background served as controls. Transgenic UNC-54(mut)::GFP animals were indistinguishable from wild-type, GFP or UNC-54(wt)::GFP control worms in terms of their body morphology (not shown) and they had normal muscle cell morphology and longitudinal distribution of the myofilaments (Figure 1B), consistent with the mild alteration seen in patients' muscle biopsies [20].…”
Section: Letter To the Editorsupporting
confidence: 56%
See 1 more Smart Citation
“…Because the human mutation has an autosomal dominant inheritance pattern, we generated transgenic animals expressing UNC-54(mut)::GFP in a wild-type genetic background; worms expressing GFP alone and UNC-54(wt)::GFP fusion protein in the same wild-type background served as controls. Transgenic UNC-54(mut)::GFP animals were indistinguishable from wild-type, GFP or UNC-54(wt)::GFP control worms in terms of their body morphology (not shown) and they had normal muscle cell morphology and longitudinal distribution of the myofilaments (Figure 1B), consistent with the mild alteration seen in patients' muscle biopsies [20].…”
Section: Letter To the Editorsupporting
confidence: 56%
“…Previous studies have shown that introducing proline residues in the MYH7 protein interferes with myosin self-assembly [18,21]. Moreover, most MYH7 mutations associated with distal myopathy are located in the mid-rod region of the protein, within exons 32-36 [22], and this is where the c.4679G>C mutation lies [20]. To test whether the p.R1460P change also causes such alteration, we expressed in worm muscle cells an UNC-54::GFP fusion protein with a corresponding proline change to that identified in the patients (UNC-54(mut)::GFP) (Figure 1A).…”
Section: Letter To the Editormentioning
confidence: 99%
“…In our series of TK2 patients although no clear pattern of fat infiltration was detected, we have identified some radiological common features, as the involvement of the sartorius muscle in all cases. This muscle is usually spared until late stages in many genetic muscle diseases (is only affected early in some myofibrillar myopathies, in the Laing distal myopathy and in RYR1-related myopathies (encodes for ryanodine receptor 1 protein) [12, 2527]), so this finding could be helpful for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been reported repeatedly, but discrepancies in relation to the muscles preferentially affected in the distinct regions are often left unexplained. For example, some reports have highlighted the involvement of the gluteus maximus in the pelvic region [12], while others have postulated a predominance of the gluteus minimus [11]; in the thighs, an earlier and more severe affectation of the sartorius and vastii was highlighted in some studies [7,12], yet elsewhere the involvement of the adductor magnus and the short head of the biceps, in addition to the sartorius, was emphasized [11]. In the legs, early reports suggested that the calf muscles remained well preserved or that they were only affected at more advanced stages [6,22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the traditional early onset anterior distal myopathy, alternative phenotypic variants have been successively reported, with axial features such as scoliosis/rigid spine, bent spine or dropped head syndromes, scapulo-peroneal syndromes and disto-proximal myopathies [4,[6][7][8][9][10][11]. Asymptomatic carriers of MYH7 mutations have also been reported [6,12], as well as severe forms complicated with respiratory insufficiency [4,7,11] and cases of associated cardiomyopathy [4,[13][14][15][16][17], widening the spectrum and complexity of this disorder.…”
Section: Introductionmentioning
confidence: 99%